The son [compact disc, unabridged] : a novel - Meyer, Philipp, 1974- (HarperAudio, 2013)
An utterly transporting novel that maps the legacy of violence in the American West through the lives of the McCulloughs, an ambitious family as resilient and dangerous as the land they claim.